Novel Seleno- and Thio-Urea Containing Dihydropyrrol-2-One Analogues as Antibacterial Agents - Shekh Sabir; Tsz Tin Yu; Rajesh Kuppusamy; Basmah Almohaywi; George Iskander; Theerthankar Das; Mark D. P. Willcox; David StClair Black; Naresh Kumar (MDPI AG, 2021)
The quorum sensing (QS) system in multi-drug-resistant bacteria such as P. aeruginosa is primarily responsible for the development of antibiotic resistance and is considered an attractive target for antimicrobial drug discovery. In this study, we synthesised a series of novel selenourea and thiourea-containing dihydropyrrol-2-one (DHP) analogues as LasR antagonists. The selenium DHP derivatives displayed significantly better quorum-sensing inhibition (QSI) activities than the corresponding sulphur analogues. The most potent analogue 3e efficiently inhibited the las QS system by 81% at 125 µM and 53% at 31 µM. Additionally, all the compounds were screened for their minimum inhibitory concentration (MIC) against the Gram-positive bacterium S. aureus, and interestingly, only the selenium analogues showed antibacterial activity, with 3c and 3e being the most potent with a MIC of 15.6 µM.